STUDI PENGEMBANGAN KAWASAN HUTAN LINDUNG GUNUNG MAHAWU MENJADI TAHURA - M. Ali Liambana; H. D. Walangitan; S. P. Ratag (COCOS, 2017)
ABSTRACT   This study aims to describe the biophysical and socio-economic conditions of Mount Mahawoe Protected Forest area and examine the strategy of the development of Mount Mahawoe Protected Forest area into the Great Forest Park area in terms of policy, institutional and potential of the area.This research was conducted by using survey method and interview to formal and informal parties by using open question questionnaire. Based on the SWOT analysis, there are 20 (two pulse strategies) that can be taken as an alternative strategy in achieving the objectives of Mahawoe Mountain forest area development into Tahura such as maintaining community commitment and participation, developing the role of NGOs and community leaders around the Mahawoe Mountain area in forest area development activities, establishes priority target locations that directly impact the protection of the hydrological system, develops species of economic and ecological value, builds stakeholder participation and cooperation in controlling the sale and purchase of land in the Mount Mahawoe protected forest area.     Keywords : Mount Mahawoe, Protected Forest, and Tahura.